Amid ant trails, the emergence of the subject: The psychoterapeutic group in the school context Abstract: The medical discourse has permeated schools as for proposing medication - Cury Junior, Joao Elias [UNESP] (Centro Univ La Salle, 2015)
The medical discourse has permeated schools as for proposing medication to solve impasses of misconduct by students, besides those well-known disciplinary strategies aiming to model behaviors. The article reflects on this context by presenting an experience carried out in a public school, among 5th graders, in the form of psychotherapeutic group, having Freud and Lacan's psychoanalysis oriented its trajectory. One of the effects of this device was the repositioning of some of its participants concerning their impasses in the school context.
Keywords: Education; Psychoanalysis; Psychotherapeutic group; Collective health